A Time Bomb Lies Buried Fiji's Road to Independence, 1960-1970 - V. Lal, Brij (SSGM Monograph, 2008)
A Time Bomb Lies Buried discusses the debates which took place in Suva and London as well as the politics and processes which led Fiji to independence in 1970 after 96 years of colonial rule. It provides an essential background to understanding the crises and convulsions which have haunted Fiji ever since in its search for a constitutional settlement for its multiethnic population.